PENERAPAN METODE CERITA ALKITAB OLEH PENYULUH AGAMA KRISTEN DALAM PEMBENTUKAN KARAKTER KRISTEN ANAK DI DESA UJUNG TANDUK KECAMATAN LAGUBOTI - Sania Pasaribu; Lasmaria Lumbantobing; Agnes Novianti Permata sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine whether the application of the Bible story method by Christian religious instructors has a positive and significant influence on the formation of Christian character in children in Ujung Tanduk Village, Laguboti District. This study employed a quantitative approach using a pre-experimental design, specifically the One-Group Pretest-Posttest Design. The study population consisted of children in Ujung Tanduk Village, Laguboti District, with a sample size of 30 children. A questionnaire served as the research instrument. Instrument validity was tested using Pearson's Product Moment formula, while reliability was assessed using Cronbach's Alpha. Data analysis was conducted using SPSS (Statistical Product and Service Solutions) version 23 software via the Paired Sample T-Test. The results indicate that the application of the Bible story method by Christian religious instructors has a positive and significant influence on the formation of Christian character in children in Ujung Tanduk Village, Laguboti District. This is evidenced by the increase in the mean score from 56.3667 in the pre-test to 70.6667 in the post-test, representing an increase of 14.3000. Hypothesis testing using the Paired Sample T-Test yielded a significance value (Sig. 2-tailed) of 0.000 (less than 0.05); consequently, the null hypothesis (H₀) was rejected and the alternative hypothesis (H₁) was accepted. Thus, it can be concluded that the application of the Bible story method by Christian religious instructors has a positive and significant influence on the formation of Christian character in children in Ujung Tanduk Village, Laguboti District.